A god in ruins : a novel - Atkinson, Kate (Little, Brown and Company, 2015)
"Kate Atkinson's dazzling Life After Life explored the possibility of infinite chances and the power of choices, following Ursula Todd as she lived through the turbulent events of the last century over and over again. A GOD IN RUINS tells the dramatic story of the 20th Century through Ursula's beloved younger brother Teddy--would-be poet, heroic pilot, husband, father, and grandfather-as he navigates the perils and progress of a rapidly changing world. After all that Teddy endures in battle, his greatest challenge is living in a future he never expected to have" --